Kathakaḷipṟabhāvaṃ sāhityakrtikaḷil - Krṣṇakkaimmaḷ, Aymanaṃ (Aymanaṃ Krṣṇakkaimmaḷ ; Vitaraṇaṃ, Nāṣanal Bukksṯāḷ, 1981)
Articles interpreting diverse literary situations from the aesthetic viewpoint of Kathakali, classical dance form of Kerala.